(untitled) (Linguostylistic Studies, 2015)
The article is devoted to comparative analysis of semantic features of individual author’s neologisms of B.-I. Antonych and I. Kalynets. We select the most representative groups of innovations in poetry B.-I. Antonych and I. Kalynets to detect the most relevant for them fragments extralinguistic reality and identify common and different trends of individual author’s word creation of poets. It was found that B.-I. Antonych and I. Kalynets most actively created author’s nomination of animals, temporal concepts, landscape elements, as well as innovations with color, quantitative component and «star». Occasionalisms these groups are represented in the works of both poets. Author’s nominations of abstract concepts, sound effects are specific in idiostyle of B.-I. Antonych. Individual author names of persons, specific items and plants are specific in idiostyle of I. Kalynets. For word creation of both poets characteristic influence of folklore. Key words: individual author’s neologism, occasionalism, innovation, the author’s nomination, semantics, comparative analysis. References